The global macroeconomic burden of road injuries: estimates and projections for 166 countries - Chen, Simiao; Kuhn, Michael; Prettner, Klaus; Bloom, David E. (The lancet. Planetary health, 2019)
Summary Background Road injuries are among the ten leading causes of death worldwide and also impede economic wellbeing and macroeconomic performance. Beyond medical data on the incidence of road injuries and their resulting morbidity and mortality, a detailed understanding of their economic implications is a prerequisite for sound, evidence-based policy making. We aimed to determine global macroeconomic costs of road traffic injuries and their cross-country distribution. Methods We calculated the economic burden of all road traffic-related injuries for 166 countries by use of a macroeconomic model that accounts for the effect of fatal and non-fatal injuries on labour supply, age-specific differences in education and experience of those who are affected by road accidents, and the diversion of injury-related treatment expenses from savings, which results in lower investment. Findings We estimated that road injuries will cost the world economy US$1·8 trillion (constant 2010 US$) in 2015-30, which is equivalent to an annual tax of 0·12% on global gross domestic product. Although low-income and middle-income countries have the largest health burden, their share of the economic burden of road injuries is only 46·4% of the global loss, reflecting in part higher productivity (and earnings) in high-income countries, but also prominently higher treatment costs. Our results also indicate that treatment costs account for a greater proportion of the economic burden in high-income countries than in low-income countries. Interpretation The macroeconomic burden of road injuries is sizeable and distributed unequally across countries and world regions. This finding suggests a case for nuanced policy making. Our framework should provide a good starting point for the more detailed analysis of policies both at country level and across different countries. Funding National Institute on Aging.